Penggunaan Model Pembelajaran Contextual Teaching And Learning (CTL) Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Materi PPKN Keberagaman Sosial, Budaya, dan Ekonomi Masyarakat - Desi Ernawati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The problem of the value of student learning outcomes in PPKn lessons on the subject of social, cultural, and economic diversity of the community which is still low and the average value has not reached the KKM, is the basis for this research. Based on the results of observations made by researchers, one of the obstacles faced in Civics learning is about an ineffective learning model. To overcome this, researchers use a CTL (Contextual Teaching and Learning) learning approach to improve Civics learning outcomes material Diversity social, cultural, and economic community in SD Negeri Sengon 03, Tanjung District, Brebes Regency. This type of research uses classroom action research with two cycles. The results of the first cycle reflection, the achievement of the average score only reached 70, learning completeness only reached 57%. Only 19 students completed from 33 students. While the results of the reflection in the second cycle, the average value increased, namely 78 or 89%. So it can be concluded that by applying the CTL learning model, it can improve the learning outcomes of Civics on the subject of social, cultural and economic diversity of the community.